Environmentally benign alginate extraction and fibres spinning from different European Brown algae species - Silva, Mariana P.; Badruddin, Ishrat Jahan; Tonon, Thierry; Rahatekar, Sameer S.; Gomez, Leonardo D. (Elsevier, 2023)
Applications of natural fibres are expanding, and sustainable alternatives are needed to support this growing demand. We investigated the production of fibres using alginates from Saccharina latissima (SAC), Laminaria digitata (LAM), Sacchoriza polyschides (SACC), and Himanthalia spp. (HIM). After extraction (3 % w/v biomass) using a sustainable protocol based on citric acid, crude alginate represented 61–65 % of the biomass dry weight for SAC and LAM, and 34–41 % for SACC and HIM when experiments were performed at small scale (1.5 g of starting material). Interestingly, scaling-up extraction (60 g of starting material) decreased yields to 26–30 %. SAC and LAM alginates had the highest M/G (mannuronic acid/guluronic acid) ratios and molecular weights when compared to those from SACC and HIM (M/G:1.98 and 2.23, MW: 302 and 362 kDa, vs 1.83 and 1.86, 268 and 168 kDa). When the four types of alginates were tested for spinning fibres cross-linked with CaCl2, only SAC and LAM alginates produced fibres. These fibres showed no clumps or cracks under stretching action and presented a similar Young's modulus (2.4 and 2.0 GPa). We have demonstrated that alginate extracted from S. latissima and L. digitata can be successfully spun into functional fibres cross-linked with CaCl2.
Keywords: Saccharina latissima; Laminaria digitata; Sacchoriza polyschides; Himanthalia spp; Alginate; Fibre; Wet spinning